2023
DOI: 10.1038/s41598-023-29210-x
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signaling during Marek’s disease in chickens

Abstract: Purinergic receptors (PRs) have been reported as potential therapeutic targets for many viral infections including herpesviruses, which urges the investigation into their role in Marek’s disease (MD), a herpesvirus induced cancer in chickens that is an important pathogen for the poultry industry. MD is caused by MD virus (MDV) that has a similar viral life cycle as human varicella zoster virus in that it is shed from infected epithelial skin cells and enters the host through the respiratory route. In this repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 140 publications
0
2
0
Order By: Relevance
“…In a recent study 132 , the sulfated polysaccharide extract ulvans from Ulva armoricana was verified to exert antiviral activity by limiting the replication/dissemination of viruses or stimulating the innate immune system of hosts, which may be an alternative to drug therapy for MDV infection. A study on the differential expression of purinergic receptors (PRs) in response to MDV infection and disease progression has demonstrated their crucial role in the process of https://doi.org/10.1038/s41541-024-00905-0 disease; PRs may provide another potential target for MD therapy 133 . The generation of breeding chicken lines with more robust immune resistance to MDV may be another effective strategy to address the current epidemic and emerging viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study 132 , the sulfated polysaccharide extract ulvans from Ulva armoricana was verified to exert antiviral activity by limiting the replication/dissemination of viruses or stimulating the innate immune system of hosts, which may be an alternative to drug therapy for MDV infection. A study on the differential expression of purinergic receptors (PRs) in response to MDV infection and disease progression has demonstrated their crucial role in the process of https://doi.org/10.1038/s41541-024-00905-0 disease; PRs may provide another potential target for MD therapy 133 . The generation of breeding chicken lines with more robust immune resistance to MDV may be another effective strategy to address the current epidemic and emerging viruses.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, alternative treatments like early innate responses and Tolllike receptor ligands have being explored to prevent viral diseases in poultry animals [120]. On this basis, Bavananthasivam et al [61] found that encapsulating TLR ligands in PLGA-NPs enhances IFN-γ and IL-1β expression, promoting prolonged innate responses and systemic immune responses against Marek's disease virus (MDV) in chickens.…”
Section: Organic Nmsmentioning
confidence: 99%